2004
DOI: 10.1074/jbc.m408100200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Compartmentalization of the Calpain/Calpastatin Network with the Endoplasmic Reticulum and Golgi Apparatus

Abstract: Calpain, a calcium-activated cysteine protease, is involved in modulating a variety of cell activities such as shape change, mobility, and apoptosis. The two ubiquitous isoforms of this protease, calpain I and II, are considered to be cytosolic proteins that can translocate to various sites in the cell. The activity of calpain is modulated by two regulatory proteins, calpastatin, the specific endogenous inhibitor of calpain, and the 28-kDa regulatory subunit. Using velocity gradient centrifugation, the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 47 publications
6
68
0
Order By: Relevance
“…Ca 2q -dependent binding of the fulllength small subunit to phospholipids had only a four-to eight-fold lower affinity than the Ca 2q -dependent binding of the heterodimer to phospholipids (Table 3). These in vitro results are consistent with our previous observation of the Ca 2q -dependent translocation of an overexpressed small subunit to cellular membranes (Gil-Parrado et al, 2003) and the recently reported association of the small subunit with the endoplasmic reticulum and the Golgi apparatus (Hood et al, 2004). The ;600-fold reduced phospholipid affinity of the N-terminally truncated single small subunit, (DV)S, clearly underlines the essential contribution of domain V to lipid binding of the small subunit.…”
Section: Lipid-binding Sites Of M-calpain: Roles Of Domain V and The supporting
confidence: 93%
See 2 more Smart Citations
“…Ca 2q -dependent binding of the fulllength small subunit to phospholipids had only a four-to eight-fold lower affinity than the Ca 2q -dependent binding of the heterodimer to phospholipids (Table 3). These in vitro results are consistent with our previous observation of the Ca 2q -dependent translocation of an overexpressed small subunit to cellular membranes (Gil-Parrado et al, 2003) and the recently reported association of the small subunit with the endoplasmic reticulum and the Golgi apparatus (Hood et al, 2004). The ;600-fold reduced phospholipid affinity of the N-terminally truncated single small subunit, (DV)S, clearly underlines the essential contribution of domain V to lipid binding of the small subunit.…”
Section: Lipid-binding Sites Of M-calpain: Roles Of Domain V and The supporting
confidence: 93%
“…Recent work revealed an increased association of calpains with the endoplasmic reticulum and the Golgi apparatus after stimulation of cells with laminin. In these studies m-calpain co-localised with phosphatidylinositol-4,5-bisphosphate (PIP 2 ) and with membrane lipid rafts (Hood et al, 2004). However, Zalewska et al (2004) reported that inside-out erythrocyte vesicles did not lower the Ca 2q requirement for autolysis of m-and m-calpain.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This association is hydrophobic; therefore, calpains reside mainly on the cytosolic side of the organelle membranes. [28][29][30][31] However, recent findings indicate that calpain 1 is also present within the mitochondria. 23 It has been suggested that OMM permeabilization should precede AIF processing during apoptosis, as the overexpression of Bcl-2 and Bcl-X L prevented both AIF cleavage and release.…”
Section: Discussionmentioning
confidence: 99%
“…In early studies, calpain and calpastatin were identified in the ER isolated from A549 lung adenocarcinoma cells (8). Topological studies suggested that m-calpain was oriented with the catalytic 80-kDa subunit mostly exposed to the cytolosic side of the ER membrane, along with the regulatory regions of calpastatin (9).…”
mentioning
confidence: 99%